Typologies of women in supply chains to guide gender equity actions: The case of Volcafe in El Paraíso - Soto, Fernanda; González, Silvia; Wiegel, Jennifer (2024)
This study is a collaboration between the Alliance of Bioversity International and the International Center for Tropical Agriculture (CIAT), Volcafe and Swisscontact in the framework of the Gender Equity and Rethinking Food Markets initiatives, both supported by donors from the CGIAR Trust Fund. This study constructed a typology of women involved in Volcafe's coffee value chain based on their role in it, their relationship with the company and their sociocultural position. This analysis makes it possible to identify different groups of women to guide targeted interventions that address the different challenges they face. Empowering women in this chain is key not only to improving their well-being, but also to ensuring the sustainability and productivity of the sector. By implementing strategies based on this typology, Volcafe and Swisscontact have the opportunity to lead a significant shift towards gender equality in coffee farming.